Effects of Counseling on the Preparation of Labor For pain of Labor - Titin Novayanti Dey; Yurizki Telova (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Mothers who get additional information during pregnancy about how preparations and processes during labor later will greatly assist mothers in understanding kedaannya and reduce excessive anxiety. This study aims to analyze the influence of counseling on delivery preparation for labor pain in the intervention group and control group. This research is a kind of quasi experiment research, that is difference of mother primigravida given counseling about delivery preparation as intervention group and mother primigravida not given counseling about delivery preparation as control group. A sample of 15 people in the intervention group and 15 people in the control group. Then filled the questionnaire VAS (visual analogue scale) to assess pain after childbirth. Data were analyzed using mann-whitney test. The results showed that all control groups felt very severe pain level at the time of delivery of 15 people (60.0%) while the intervention group of pain level that was felt during the most labor was very heavy pain 10 people (40.0%), severe pain 4 people (100%) and moderate pain 1 person (100%).